Linguistic Interviewing as a Method for Determining the Degree of Representativeness of Antonymous Pairs in the English Language - Lytvyn, Oksana (East European Journal of Psycholinguistics, 2017)
In this article, the degree of representativeness of the examples (pairs of lexical units) which illustrate antonymous relations in the English language has been determined, utilizing the method of linguistic interviewing. The article presents the procedure and the results of the psycholinguistic experiment conducted. The peculiarities of the method of linguistic interviewing as a type of psycholinguistic experiment have been defined. A selection of antonymous pairs provided by leading linguists in the area of lexical semantics as illustrative examples in thirteen English-language linguistic works (monographs, textbooks and linguistic encyclopaedias) serves as the material for the experiment. All of the 101 respondents are scholars in the field of linguistics (Candidates and Doctors of Philological Sciences, as well as postgraduate students from the higher educational establishments of Ukraine), and are native speakers of Ukrainian, English being their first foreign language. In the experiment, the respondents were to identify which pairs of lexical items given in the list illustrate the relation of antonymy. Analyzing the results of linguistic interviewing, we were able to determine the pairs of antonyms with the highest and the lowest degrees of representativeness. The research demonstrated that gradable and complementary antonyms, mainly adjectives, have the highest degree of representativeness. In addition, we identified certain correlations with the results of linguistic interviewing conducted earlier, the respondents being linguistics scholars, including university and college professors, who are native speakers of English from five English-speaking countries. References Bruner, J. S., Goodnow, J. J. and Austin, G. A. (1986). A Study of Thinking. New Brunswick; New Jersey: Transaction Publishers. Cruse, D. A. (1987). Lexical Semantics. Cambridge: Cambridge University Press. Kotys, O. (2014). Psykholinhvistychnyi esperyment yak metod doslidzhennia pryrodnoiyi katehorii [Psycholinguistic experiment as a method of investigating a natural category]. East European Journal of Psycholinguistics, 1(1), 114–121. Levytskyi, V. V. and Sternin, I. A. (1989). Eskperimentalnyie Metody v Semasiologii [Experimental Methods in Semasiology]. Voronezh: Voronezh University Publishers. Lytvyn, O. L. (2014). Leksychne napovnennia katehorii antonimii (za danymy anhlomovnykh linhvistychnykh prats) [Lexical content of the category of antonymy (based on a selection of English-language linguistic works)]. Nova Filolohiya, 64, 49– 54. Lytvyn, O. L. (2015). Doslidzhennia antonimichnykh vindoshen u psykholinhvistychnomu eksperymenti [A study of antonymic relations as evidenced in a psycholinguistic experiment]. Naukovyi Visnyk Skhidnoievropeiskoho Natsionalnoho Universytetu imeni Lesi Ukrainky: Filolohichni Nauky: Movoznavstvo, 4(305), 71–75. Rosch, E. H. (1973). Natural categories. Cognitive Psychology, 4(3), 328–350. Rosch, E. H. (1975). Cognitive representations of semantic categories. Journal of Experimental Psychology: General, 104(3), 192–233.